PENGEMBANGAN MEDIA KOMIK TEMATIK ISLAMI - Nurul Fadillah; Nirwana Anas; Rora Rizky Wandini (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to develop Islamic Thematic Comics as a valid, practical and effective learning media. The methods used in this study were validation sheets, questionnaires and learning outcomes tests. The type of this research is R&R research with Borg and Gall research design. The results showed that the Islamic Thematic Comic product based on the value given by the valid validator obtained a value of 94.01% in the "Very Eligible" category, the practicality level obtained a value of 77.60% in the "Very Eligible" category and was declared effective with an increase in the value of 76.00 and after using Comics, which is 81.67. Based on the results of the tests carried out, it can be concluded that the development of Islamic Thematic Comics products to improve student learning outcomes is declared valid, practical, and effective.Keywords: Islamic, Thematic, Comic Media.